Erich Kosiol's Pagatoric Theory as A Contribution To Cash Recognition of Events in Accounting - Ewa ŚNIEŻEK (Communications of International Proceedings, 2024)
For years, not only in Europe, but also around the world, the literature has too rarely pointed out the significant influence of accounting theory, and German balance sheet theories in particular, on the “philosophy of thinking” in the process of shaping modern financial statements.  There is still a research gap in examining the links between German balance sheet theories and contemporary approaches to business reporting, especially in the area of the funds and cash approach.  This article addresses the work of Erich Kosiol, a pioneer of pagatoric theory, who formulated the elements of a systematic, unified and closed theory of accounting, valuation and balance sheet based on the research of Sganzini, Schmalenbach and Walb. Literature analysis and a deductive approach supported by the special theory approach were used as a research method. The author showed that researchers developing dynamic balance sheet theories have made significant contributions to the development of financial reporting, especially in its s dynamic area. The literal application of the dynamic balance sheet in today's economic reality and its global environment obviously does not bring practical and measurable informational benefits. However, using the example of the pagatoric theory of E. Kosiola showed, the theories of the dynamic balance sheet have become a cornerstone for the development of fund and cash flow reporting, providing an important analytical basis for its concept.
Keywords: accounting history; cash basis; balance sheet theories; pagatoric theory; dynamic balance sheet; cash recognition of entity operations.